Cutaneous manifestations in idiopathic inflammatory myopathies - Juan Sanz-Correa; Tatiana Cobo-Ibáñez; Iolanda Prats Caelles (Publicaciones Permanyer, 2022)
Idiopathic inflammatory myopathies (IIMs), also known as autoimmune myositis, are a rare group of autoimmune disorders with a heterogenoeous spectrum of muscular and extramuscular involvement. IIM can be classified into several subgroups: dermatomyositis (DM), including clinically amyopathic DM, antisynthetase syndrome (ASS), immune-mediated necrotizing myopathy, inclusion body myositis, polymyositis, and overlap myositis (OM). Skin disease is a defining feature of DM, also present in AAS and OM. Lesions of DM are very varied but many share common histological features that are very useful for an early diagnosis of IIM when cutaneous involvement precedes other symptoms. Although the characteristic signs of DM are heliotrope rash, Gottron's papules, and Gottron's sign, there are a multitude of other cutaneous findings that can suggest a diagnosis of DM. Myositis-specific autoantibodies an myositis-associated autoantibodies have been identified in IIM. The former is only present in IIM and the latter can occur not only in IIM but also in other autoimmune disorders such as systemic lupus erythematosus, Sjögren syndrome, or systemic sclerosis. Myositis autoantibodies identify different clinical phenotypes, so they are very valuable in improving diagnosis and classification of IIM patients. This article first discusses the cutaneous findings of DM and then two particular phenotypes, MDA-5 DM, and AAS. Finally, OM according to myositis-associated autoantibodies is reviewed.